2021
DOI: 10.1093/mnras/stab2172
|View full text |Cite
|
Sign up to set email alerts
|

Global simulations of tidal disruption event disc formation via stream injection in GRRMHD

Abstract: We use the general relativistic radiation magnetohydrodynamics code KORAL to simulate the accretion disk formation resulting from the tidal disruption of a solar mass star around a super massive black hole (BH) of mass 106 M⊙. We simulate the disruption of artificially more bound stars with orbital eccentricity e ≤ 0.99 (compared to the more realistic case of parabolic orbits with e = 1) on close orbits with impact parameter β ≥ 3. We use a novel method of injecting the tidal stream into the domain, and we beg… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 80 publications
0
8
0
Order By: Relevance
“…It is worth noting that radio emission in "non-jetted" TDEs (TDEs with no highly relativistic jet) typically appears > 30 days after the peak emission. This may simply be due to the initially turbulent evolution of the disk, which may suppress the formation of a funnel region, through which the gas may be accelerated into a jet (Curd 2021). However, Bonnerot & Lu (2020) present models which appear to have formed a funnel.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is worth noting that radio emission in "non-jetted" TDEs (TDEs with no highly relativistic jet) typically appears > 30 days after the peak emission. This may simply be due to the initially turbulent evolution of the disk, which may suppress the formation of a funnel region, through which the gas may be accelerated into a jet (Curd 2021). However, Bonnerot & Lu (2020) present models which appear to have formed a funnel.…”
Section: Introductionmentioning
confidence: 99%
“…For example, a solar mass star disrupted around a 10 6 M BH will have a peak fallback rate that is ∼ 100 times the Eddington rate, and the fallback rate should remain above Eddington for a few fallback times. Hydrodynamic simulations of the early stages of disk formation in a TDE suggest that as much as 20% of the returning stream may actually cross the horizon through an accretion flow; however, the current library of published simulations has yet to cover a substantial range of the TDE parameter space and the effects of magnetism have largely been ignored in long term simulations (Ramirez-Ruiz & Rosswog 2009;Guillochon et al 2014;Shiokawa et al 2015;Hayasaki et al 2016;Bonnerot et al 2016;Liptai et al 2019;Bonnerot & Lu 2020;Bonnerot et al 2021;Curd 2021;Andalman et al 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Recent global simulations that track the postshock gas circularization seem to indicate that the stream-stream collision can efficiently redistribute debris angular momentum (Bonnerot & Stone 2021;Curd 2021;Andalman et al 2022;Steinberg & Stone 2022). In fact, recent work has suggested that the fallback debris may be slow to circularize and form an accretion disk, implying that the majority of emission could be powered by various shocks, including those from stream selfinteraction.…”
Section: Introductionmentioning
confidence: 99%
“…The a • distribution is poorly understood at present, with most existing measurements arising from a single technique: iron Kα reflection spectroscopy (Reynolds 2014). The SMBH spin is imprinted on TDE observables in various ways, e.g., relativistic precessions (Stone & Loeb 2012;Guillochon & Ramirez-Ruiz 2015;Hayasaki et al 2016;Liptai et al 2019;Curd 2021;Andalman et al 2022), the disk thermal X-ray spectrum (McClintock et al 2006;Done et al 2012), the TDE rate (Kesden 2012), and quasiperiodic oscillations in the X-ray spectrum (Dheeraj et al 2019), raising the possibility of obtaining independent SMBH spin constraints, with different uncertainties and biases than those of the status quo.…”
Section: Introductionmentioning
confidence: 99%